ANALISIS CLUSTER PENGUNJUNG TEMPAT WISATA (Studi Kasus: Pantai Panjang Bengkulu) - Mimi Kurnia Nengsih; Yesi Indian Ariska (UNIVED Press, 2020)
Mimi Kurnia Nengsih, Yesi Indian Ariska; This study aims to classify visitors to Bengkulu long beach tourism. This research was conducted through direct observation, interviews and questionnaires with 30 respondents. The analysis used is cluster analysis. The results obtained are Bengkulu Long Beach tourist attractions in the group based on Gender, Education, Age, Place of Origin and Income. Based on the F value in the Anova analysis it is known that the difference in visitors based on education has increasingly smaller differences in the clusters formed. In this study it appears that visitors are dominated by high school education. Other variables that form the basis of grouping visitors such as Gender, Age, Place of Origin and Income there are large differences in cluster formation. Keywords: Long Beach, Tourism, Cluster